Functional dissection of HGGT and HPT in barley vitamin E biosynthesis via CRISPR/Cas9-enabled genome editing. (24th June 2020) - Zeng, Zhanghui; Han, Ning; Liu, Cuicui; Buerte, B; Zhou, Chenlu; Chen, Jianshu; Wang, Mengyao; Zhang, Yuhong; Tang, Yawei; Zhu, Muyuan; Wang, Junhui; Yang, Yinong; et al.
Abstract: Background and Aims: Vitamin E (tocochromanol) is a lipid-soluble antioxidant and an essential nutrient for human health. Among cereal crops, barley ( Hordeum vulgare ) contains a high level of vitamin E, which includes both tocopherols and tocotrienols. Although the vitamin E biosynthetic pathway has been characterized in dicots, such as Arabidopsis, which only accumulate tocopherols, knowledge regarding vitamin E biosynthesis in monocots is limited because of the lack of functional mutants. This study aimed to obtain gene knockout mutants to elucidate the genetic control of vitamin E composition in barley. Methods: Targeted knockout mutations of HvHPT and HvHGGT in barley were created with CRISPR/Cas9-enabled genome editing. High-performance liquid chromatography (HPLC) was performed to analyse the content of tocochromanol isomers in transgene-free homozygous Hvhpt and Hvhggt mutants. Key Results: Mutagenesis efficiency among T0 regenerated plantlets was 50–65 % as a result of two simultaneously expressed guide RNAs targeting each gene; most of the mutations were stably inherited by the next generation. The transgene-free homozygous mutants of Hvhpt and Hvhggt exhibited decreased grain size and weight, and the HvHGGT mutation led to a shrunken phenotype and significantly lower total starch content in grains. HPLC analysis revealed that targeted mutation of HvHPT significantly reduced the content of both tocopherols and tocotrienols, whereas mutations in HvHGGT completely blocked tocotrienol biosynthesis in barley grains. Transient overexpression of an HvHPT homologue in tobacco leaves significantly increased the production of γ- and δ-tocopherols, which may partly explain why targeted mutation of HvHPT in barley grains did not eliminate tocopherol production. Conclusions: Our results functionally validated that HvHGGT is the only committed gene for the production of tocotrienols, whereas HvHPT is partly responsible for tocopherol biosynthesis in barley.